2016
DOI: 10.1096/fj.201600144rr
|View full text |Cite
|
Sign up to set email alerts
|

D‐series resolvins inhibit murine abdominal aortic aneurysm formation and increase M2 macrophage polarization

Abstract: The role of resolvins in abdominal aortic aneurysm (AAA) has not been established. We hypothesized that treatment with D-series resolvins (RvD2 or RvD1) would attenuate murine AAA formation through alterations in macrophage polarization and cytokine expression. Male C57/B6 mice (n = 9 per group) 8 to 12 wk old received RvD2 (100 ng/kg/treatment), RvD1 (100 ng/kg/treatment), or vehicle only every third day beginning 3 d before abdominal aortic perfusion with elastase as prevention. Aortas were collected 14 d af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 45 publications
5
100
0
Order By: Relevance
“…S2), it was not apparently increased in abundance during coagulation. RvD2 is produced by human adipocytes (14) and other human tissues (1517), prevents secondary thrombosis and necrosis in dermal burn wounds (18), and is protective in abdominal aortic aneurysm (19). Principal component analysis (PCA) confirmed that the production of TXB 2 , PGD 2 , and LTB 4 were associated with early time points, whereas the specific SPM cluster was associated with later times during coagulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2), it was not apparently increased in abundance during coagulation. RvD2 is produced by human adipocytes (14) and other human tissues (1517), prevents secondary thrombosis and necrosis in dermal burn wounds (18), and is protective in abdominal aortic aneurysm (19). Principal component analysis (PCA) confirmed that the production of TXB 2 , PGD 2 , and LTB 4 were associated with early time points, whereas the specific SPM cluster was associated with later times during coagulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, clearing of adenosine increased platelet-neutrophil aggregation and the biosynthesis of RvD3, RvD4, and RvD6, which enabled quantitation of the full spectrum of D-series resolvins, except for RvD2, which was not increased during whole-blood coagulation (Fig. 1), yet is protective against abdominal aortic aneurysm (19) and secondary thrombosis and necrosis in thermal burn wounds (18). SPMs also stimulate macrophages to phagocytize thrombi in the form of fibrin clots (53), which may facilitate the remodeling of clots or their removal.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with n-3 PUFA has previously been implicated as a potential therapeutic strategy in this context (Wales, Kavazos et al 2014). Pope and colleagues demonstrated that systemic administration of either RvD1 or RvD2 (100 ng/kg IP every 3 days) significantly decreased AAA formation in a surgical elastase-perfusion model, associated with preservation of elastin, reduced macrophage (but not T-cell) infiltration, a broad reduction in local inflammatory cytokine signals (TNF-α, IL-1α, IL-1β, MCP-1, CXCL-1, RANTES), increase anti-inflammatory cytokines (IL-10), and reduction in MMP activity by gelatin zymography (Pope, Salmon et al 2016). When specifically examined, RvD2 treatment resulted in a shift in aortic wall macrophage phenotype favoring M2 polarization.…”
Section: In-vivo Effects Of Spm In Animal Models Of Vascular Injurymentioning
confidence: 99%
“…The rapamycin inhibitor everolimus limited angiotensin II (AngII)‐induced AA formation in apolipoprotein E‐deficient (apoE −/− ) mice via suppressed development of bone marrow CCR2 monocytes and diminished M1 polarization . D‐series resolvins could attenuate inflammatory activities and AA formation by increasing M2 macrophage polarization . Elastin‐derived peptides (EDPs) promoted a pro‐inflammatory environment in aortic tissues and attenuated aortic dilation through induction of M1 polarization, and neutralization of EDPs.…”
Section: Introductionmentioning
confidence: 99%